2019
DOI: 10.1007/s13158-019-00245-4
|View full text |Cite|
|
Sign up to set email alerts
|

The Abecedarian Approach in a Low-Resource Urban Neighborhood in Canada: An Impact Evaluation in a Child Care Setting

Abstract: Despite the best efforts, persistent educational gaps remain between Indigenous and non-Indigenous children when they begin school. This evaluation explores the impact of the Abecedarian Approach for early education on the language development of First Nations and non-First Nations children, living in a low-resource, urban neighborhood in Canada. A treatment group received the Abecedarian Approach in a child care center, supplemented by home visiting, and comprised 20 families with 41 children of whom 51% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Interestingly, studies simultaneously engaging parents and early childhood educators are few (Greenwood et al, 2019), particularly when child language outcomes are measured. Stevens et al (2019) explored the impact of the Abecedarian approach on the language development of First Nations and non-First Nations children and found that the pre-intervention gap that existed between the two groups (on a norm referenced language measure) was completely closed by the end of the second year of the intervention.…”
Section: Parent and Preschool-focused Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies simultaneously engaging parents and early childhood educators are few (Greenwood et al, 2019), particularly when child language outcomes are measured. Stevens et al (2019) explored the impact of the Abecedarian approach on the language development of First Nations and non-First Nations children and found that the pre-intervention gap that existed between the two groups (on a norm referenced language measure) was completely closed by the end of the second year of the intervention.…”
Section: Parent and Preschool-focused Interventionsmentioning
confidence: 99%
“…Stevens et al. (2019) explored the impact of the Abecedarian approach on the language development of First Nations and non‐First Nations children and found that the pre‐intervention gap that existed between the two groups (on a norm referenced language measure) was completely closed by the end of the second year of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, under the control condition the non-FN children made slow progress and the FN children gained almost no ground. The gap between the FN treatment group and the non-FN control group at baseline was completely closed by year two of the study—at which point these two groups had identical scores [ 7 ].…”
Section: Mental Health and Social Development Effects From Abecedarian Interventionsmentioning
confidence: 99%
“…The Abecedarian Approach has been implemented in multiple countries. The Approach has been adapted and used as a birth to age three or birth to age five program in Australia, Canada, China, Denmark, France, India, Jordan, Mexico, Mongolia, Pakistan, Singapore, and Zambia [ 6 , 7 , 8 , 9 , 10 , 11 ]. Some of these uses were research studies while others were training and implementation applications.…”
Section: Introductionmentioning
confidence: 99%
“…La evaluación del lenguaje oral, la lectura y la escritura en población infantil ha tenido diversas miradas desde diferentes enfoques teóricos y procedimentales, que históricamente ha pretendido explicar la ontogenia y el desarrollo de estas áreas comunicativas en los niños (Aimacaña Toctaguano & Reinoso, 2022;Quintana Alonso, 2003;Stevens et al, 2019). La evaluación, en general, debe permitir establecer el desempeño de los sujetos, en cuanto a saberes y capacidades considerados necesarios para iniciar con éxito nuevos procesos de aprendizaje, pues se espera un adecuado desempeño de las funciones ejecutivas que son consideradas como un conjunto de procesos cognitivos, dentro de las que se encuentra el lenguaje (Delgado Reyes et al, 2022).…”
Section: Introductionunclassified